Contemporary authors cumulative index - Gale Research Inc.; Gale Research Company; Gale Group (Detroit : Gale Research Inc., 1996)
Includes references to all entries in: Contemporary authors, Contemporary authors new revision series, Something about the author, Authors in the news.
Description based on: Vol. 1-88, published 1980; title from cover.
Each vol. cumulative from v. 1.
Keywords: Literature -- 20th century -- History and criticism -- Indexes; Authors -- 20th century -- Biography -- Indexes